Practice of preventive dentistry for nursing staff in primary care (Colombia Medica, 2014)
Objectives: Determine the domain of preventive dentistry in nursing personnel assigned to a primary care unit. Methods: Prospective descriptive study, questionnaire validation, and prevalence study. In the first stage, the questionnaire for the practice of preventive dentistry (CPEP, for the term in Spanish) was validated; consistency and reliability were measured by Cronbach's alpha, Pearson's correlation, factor analysis with intra-class correlation coefficient (ICC). In the second stage, the domain in preventive dental nurses was explored. Results: The overall internal consistency of CPEP is α= 0.66, ICC= 0.64, CI95%: 0.29-0.87 (p >0.01). Twenty-one subjects in the study, average age 43, 81.0% female, average seniority of 12.5 were included. A total of 71.5% showed weak domain, 28.5% regular domain, and there was no questionnaire with good domain result. The older the subjects were, the smaller the domain; female nurses showed greater mastery of preventive dentistry (29%, CI95%: 0.1-15.1) than male nurses. Public health nurses showed greater mastery with respect to other categories (50%, CI95%: 0.56-2.8). Conclusions: The CDEP has enough consistency to explore the domain of preventive dentistry in health-care staff. The domain of preventive dentistry in primary care nursing is poor, required to strengthen to provide education in preventive dentistry to the insured population.